Beneficial Effects of Motor Imagery and Self-Talk on Service Performance in Skilled Tennis Players - Robin, Nicolas; Dominique, Laurent; Guillet-Descas, Emma; Hue, Olivier (Frontiers in Psychology, 2022)
This research aim to investigate the effects of motor imagery (MI), focused on the trajectory of the ball and the target area, and self-talk (motivational function) before the actual strike on the performance of the service in skilled tennis players. Thirty-three participants (6 females and 27 males, Mage = 15.9 years), competing in regional to national competitions, were randomly divided into three groups: Control, MI, and MI+self-talk. They performed a pre-test (25 first service), 20 acquisition sessions (physical trial, physical trial + MI and physical trial + MI+self-talk), and a post-test similar to the pre-test, in match situations. The percentage of the first service, their speed, and the efficiency scores, evaluated by experts, were use as dependant variables and indicators of performance. While there was no difference in service speed (p> .05), this study showed an improvement in the first service percentage and efficiency (all ps < .01)in the participants of the MI and MI+self-talk groups. Additionally, analyses revealed greater efficiency when MI was combined with self-talk compared to other conditions. It, therefore, seems advantageous for skilled tennis players to use MI and motivational self-talk before performing the first service balls.